2013
DOI: 10.1007/s11695-013-0887-1
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy for Morbid Obesity: 5 Years Experience from an Asian Center of Excellence

Abstract: LSG as a single-stage bariatric procedure is safe and durable, achieving weight loss and resolution of comorbidities up to 5 years. Adherence to technical details is pivotal in reducing complications associated with the initial learning phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(28 citation statements)
references
References 38 publications
2
24
0
2
Order By: Relevance
“…At any rate, these numbers suggest that postoperative complications after LSG could be proportionately influenced by the extent of the surgeons' experience. For one surgical centre, Zachariah et al reported that major complication rates dropped from 8 % for the first 50 surgeries performed to 1.68 % for the remaining 178 surgeries with statistical significance [6]. In our series, all the leakages occurred during our center's early experience (#3, 16,19,53,55) of the subject procedure.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…At any rate, these numbers suggest that postoperative complications after LSG could be proportionately influenced by the extent of the surgeons' experience. For one surgical centre, Zachariah et al reported that major complication rates dropped from 8 % for the first 50 surgeries performed to 1.68 % for the remaining 178 surgeries with statistical significance [6]. In our series, all the leakages occurred during our center's early experience (#3, 16,19,53,55) of the subject procedure.…”
Section: Discussionmentioning
confidence: 44%
“…Also, Diamantis et al reviewed the published long-term weight loss results after LSG (492 cases in 16 studies) and showed that the mean %EWL was 62.3 % [5]. Among these 16 analyzed studies, only one study was from Asia [6], thus, long-term data from Asia where LSG is a leading procedure is obviously insufficient. The first LSG in our center was performed in 2005 [7].…”
Section: Introductionmentioning
confidence: 99%
“…Cottam et al [24] 2006 126 65.3 12 46 Hamoui et al [5] 2006 118 55 24 47.3 Lee et al [21] 2007 216 49 24 59 Nocca et al [20] 2007 163 45.9 24 61.5 Weiner et al [13] 2007 120 60.7 60 NR Yang O et al [8] 2008 138 50.6 24 46 Parikh et al [12] 2008 135 60.1 12 47.3 Felberbauer et al [18] 2008 126 48.1 19 NR Rubin et al [15] 2008 120 43.5 11 NR Fuks et al [24] 2009 135 48.8 12 49.4 Stroh et al [25] 2009 144 54.5 24 NR Bobowicz et al [26] 2011 112 44.6 22 46.6 Chopra et al [9] 2011 174 48.9 36 58.9 Rawlins et al [27] 2012 49 65 60 86 Catheline et al [28] 2013 45 49.1 60 50.7 Sieber et al [29] 2013 54 43 60 57.4 Zachariah et al [10] 2013 228 37.4 60 63.7 Bellows et al [30] 2014 63 51.8 17 47.2 Boza et al [22] 2014 161 34.9 60 62.9 the size of bougies is one of the important factors contributing to durable weight loss. [11,34] The other important point to the weight loss outcome after LSG might be the changes in the plasma levels of ghrelin.…”
Section: Follow-up (Mo) %Ewlmentioning
confidence: 99%
“…[19,27] Zachariah et al published long-term follow-up (60 months) outcomes including T2DM and arterial hypertension resolution rate, which were found 66% and 100%, respectively. [23] In an- [36] 2012 121 NR 0 5.1 0 2.5 13.2 0 Gentileschi et al [37] 2012 120 NR 1.7 1.7 0 0.8 3.3 0 Catheline et al [28] 2013 45 60 3.8 1.9 0 NR 5.7 0 Zachariah et al [10] [30] 2014 63 17 0 0 0 5 11 0 Boza et al [22] 2014 161 60 0.6 0 0.6 NR 3.7 0…”
Section: Follow-up (Mo) %Ewlmentioning
confidence: 99%
“…The most important disadvantage of this surgical technique is postoperative nutritional deficiencies that require longterm follow-up (6). Since LSG is easy to learn, has fewer complication rates, and has fewer nutritional effects, it is being increasingly used in the surgical treatment of obesity (7,8).…”
Section: Introductionmentioning
confidence: 99%